Risk Factors for Recurrence after Surgical Resection of Sinonasal Inverted Papilloma - Delaine, Eugénie; Gorostidi, François; Guilcher, Pierre; Lambercy, Karma; Litzistorf, Yann; Bron, Luc; Reinhard, Antoine (International Archives of Otorhinolaryngology, 2024)
Introduction Sinonasal inverted papilloma (SNIP) is a rare benign epithelial tumor of the nasal cavity and paranasal sinuses that accounts for 0.4% and 4.7% respectively, of all tumors of this anatomical region.Objective To analyze the outcomes after surgical resection of SNIP and identify the risk factors for recurrence in a Swiss tertiary center.Methods We conducted a retrospective review of all cases of SNIP treated at the Lausanne university hospital between 2005 and 2018. All data available on the patients and tumors were collected for analysis. We studied the recurrence rate and looked for risk factors.Results We included 57 patients with a mean age of 55.5 years. There were 46 primary cases (80.7%) and 11 recurrences (19.3%). Maxillary sinus was the most frequent location (33.3%). Approximately half of the patients (52.6%) presented with a T3 tumor according to the Krouse classification. The mean recurrence rate after surgery was of 17.5% and it was more frequent among the patients in the recurrence group (45.5%) than among the primary cases (10.9%), reaching statistical significance (odds ratio [OR] = 6.8; 95% confidence interval [95%CI]: 1.5–30.8; p = 0.0165). Most patients were treated endoscopically (94.7%). Frontal sinus location, higher Krouse stage, and combined approach seemed to increase the risk of recurrence, but without statistical significance.Conclusion Difficult surgical access, as in the case of tumors located in the frontal sinus, higher stage of the disease, and previously operated cases carry the higher risk of incomplete resection and recurrence.
Keywords: sinonasal inverted papilloma; Schneiderian papilloma; recurrence; endoscopic resection; Krouse classification